The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/leu.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

Development of CLL in the TCL1 transgenic mouse model is associated with severe skewing of the T-cell compartment homologous to human CLL

Abstract: Chronic lymphocytic leukemia (CLL) cells require complex microenvironmental and immunologic interactions to survive and proliferate. Such interactions might be best recreated in animal models; however, this needs extensive verification. We therefore investigated the composition of the T-cell compartment in the El-TCL1 transgenic mouse, currently the most widely used murine model for CLL. Immunophenotyping and transplant approaches were used to define T-cell subsets at various stages of CLL. Analogous to human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
1
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 32 publications
4
92
1
3
Order By: Relevance
“…22 The TCL1 mouse was constructed to specifically overexpress the TCL1 gene in B cells using the Em-enhancer promoter system. [22][23][24]30 The mean difference between the expressed Ig V(H) genes of these mice and germ line is only 0.5%, thus the TCL1 mouse is thought to model the more aggressive, IgV(H) unmutated form of the disease in humans. 37 Lymphocytes of TCL1-mice with overt leukemia were engrafted in 10 C57BL/6 mice, as previously described.…”
Section: Identification Of P53-independent Apoptosis Inducersmentioning
confidence: 99%
See 2 more Smart Citations
“…22 The TCL1 mouse was constructed to specifically overexpress the TCL1 gene in B cells using the Em-enhancer promoter system. [22][23][24]30 The mean difference between the expressed Ig V(H) genes of these mice and germ line is only 0.5%, thus the TCL1 mouse is thought to model the more aggressive, IgV(H) unmutated form of the disease in humans. 37 Lymphocytes of TCL1-mice with overt leukemia were engrafted in 10 C57BL/6 mice, as previously described.…”
Section: Identification Of P53-independent Apoptosis Inducersmentioning
confidence: 99%
“…37 Lymphocytes of TCL1-mice with overt leukemia were engrafted in 10 C57BL/6 mice, as previously described. [22][23][24]30 However, two of them died before the start of treatment, indicating that they had advanced tumor progression. The remaining eight mice were equally divided between control (phosphate-buffered saline) and treatment arms (0.06 mg/kg actinomycin D for 14 consecutive days i.p.).…”
Section: Identification Of P53-independent Apoptosis Inducersmentioning
confidence: 99%
See 1 more Smart Citation
“…In an accelerated euTCL1 model, T-cell alterations induced by disease progression were found to be antigen-driven and clonally skewed. 42 McClanahan et al investigated CLL T-cell function in aging and accelerated euTCL1 models.…”
Section: Lessons From Preclinical Cll Modelsmentioning
confidence: 99%
“…Examining the CLL T-cell compartment has resulted in novel mechanisms for CLL progression and interest in immunotherapeutic strategies. [41][42][43] To study the dependence of CLL B cells on immune subsets, carboxyfluorescein succinimidyl ester-labeled human CLL cells were injected into NSG mice alongside various immune components, such as CD34 1 progenitor cells, mesenchymal stromal cells, or mature APCs. 44 Data demonstrated that T cells activated by allogeneic APCs were required for leukemic cell survival and proliferation.…”
Section: Lessons From Preclinical Cll Modelsmentioning
confidence: 99%